INFLUENCE OF INSTRUCTIONAL RESOURCES ON TEACHERS’ JOB PERFORMANCE AND STUDENTS ACADEMIC PERFORMANCE IN PUBLIC SECONDARY SCHOOLS FEDERAL CAPITAL TERRITORY, ABUJA, NIGERIA - Esther Amina Akuh; Victor Olugbenga Ayoko (International Journal of Business, Law and Political Science, 2025)
Objective: This study aims to assess the influence of instructional resources on teachers’ job performance and students’ academic performance in public secondary schools in the Federal Capital Territory (FCT), Abuja, Nigeria. Method: A descriptive survey and correlational research design were adopted. The sample consisted of 220 teachers and the academic results of 260 students from public senior secondary schools in FCT, Nigeria. A multi-stage sampling technique was used to select the sample, following the Research Advisor (2006) population size table. The reliability of the questionnaire was tested using the test-retest method. Data were analyzed using SPSS version 22.0, with descriptive statistics such as mean and percentage used to interpret distribution patterns. Result: Findings revealed a significant relationship between instructional resources and teachers’ job performance, as well as a significant relationship between instructional resources and students’ academic performance in public secondary schools in FCT, Abuja. Novelty: This study provides empirical evidence on the critical role of instructional resources in enhancing both teaching efficiency and student achievement in Nigerian public secondary schools. It highlights the necessity for adequate resource provision and teacher training to maximize the impact of instructional materials on educational outcomes.